Multimodal management of Fournier’s gangrene with subsequent wound closure techniques - V., Vijayalakshmi; Girieasen M., Sabari; S., Deepika; R., Kannan; Kumar, M. S. Kalyan (International Surgery Journal, 2022)
Fournier’s gangrene (FG) is a fulminant and lethal condition usually occurring in the immunocompromised, first described in 1883 by the French dermatologist Jean Alfred Fournier. It is a form of necrotizing fasciitis of the perineal, genitourinary and perianal regions mostly in males with a mortality of nearly 20-50%. It is a surgical emergency and requires early diagnosis aided by scores such as laboratory risk indicator for necrotising fasciitis (LRINEC) and FG severity index (FGSI), extensive debridement combined with supportive procedures to manage associated complications and broad-spectrum antibiotics. Management of FG thus required a multimodal approach and emphasis on reconstruction after recovery in patients who survive was crucial to improving the quality of life in these patients. Here we were presenting 7 cases of FG successfully managed at our institution, grouped under the four methods by which wound closure was achieved: fecal diversion and split skin grafting of scrotum, urinary diversion and penoscrotal split skin grafting, delayed primary closure (with and without orchidectomy) and wound healing by secondary intention.